2022
DOI: 10.1021/acs.analchem.1c04672
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Chemiluminescence Microarray Analysis Platform for Rapid and Multiplexed SARS-CoV-2 Serodiagnostics

Abstract: Lateral-flow immunoassays and laboratory diagnostic tests like enzyme-linked immunosorbent assays (ELISAs) are powerful diagnostic tools to help fight the COVID-19 pandemic using them as antigen or antibody tests. However, the need emerges for alternative bioanalytical systems that combine their favorable featuressimple, rapid, and cost-efficient point-of-care (POC) analysis of lateral-flow immunoassays and higher reliability of laboratory testswhile eliminating their disadvantages (limited sensitivity and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The total measurement time was 8 min. Recently, microfluidic devices have been developed that can perform antibody detection using only 16 µL of whole blood from the fingertip in just over 4 min [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total measurement time was 8 min. Recently, microfluidic devices have been developed that can perform antibody detection using only 16 µL of whole blood from the fingertip in just over 4 min [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Antibody-testing technologies are mainly categorized into (a) single-use lateral flow tests (immunochromatography), where the presence of antibodies is demonstrated by a color change on a paper strip, and (b) laboratory-based immunoassays that allow the processing of many specimens simultaneously [3,4]. In addition, some microarray systems have been developed for research purposes [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Microarray chips for the CL-SMIA were produced using PC foils with a thickness of 0.25 mm [28,29]. In prior studies, PC plates with a thickness of 1 mm were used [24,25,30]. Thinner material has the advantage of easier and faster processing with the cutting plotter, as fewer passes of the blade make the process faster.…”
Section: Flow-based Cl-smiamentioning
confidence: 99%
“…The volumes and flow rates of these reagents can be adjusted as needed, which makes them much more flexible for assay optimization compared to static incubated immunoassay formats [23]. Features of this newest version of MCRs are described in detail elsewhere, where it has also been shown that the MCR-R can be used for diagnostic testing [24]. Using polycarbonate (PC) as a surface enables more cost-effective and faster production of microarray chips compared to glass surfaces [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation